Effects of Weevil Infested Feed on the Fecundity and Gonadal Development of the African Catfish Clarias gariepinus (BURCHELL 1822) - Eyo, Victor Oscar; Arong, Gabriel A.; Opeh, Patience Bassey (Journal of Agricultural Science and Agrotechnology, 2022)
This study was carried out for 126 days to evaluate the effects of weevil infested feed on the fecundity and gonadal development of the African Catfish Clarias gariepinus. Six (6) tarpaulin tanks (100 by 80 by 100 cm3 ) were stocked randomly with twenty (20) healthy post fingerlings of C. gariepinus with a mean initial bulk body weight 320.58 ± 1.24 g and total length 11.62 ± 0.36 cm. Coppens feed (42% crude protein) was divided into two groups including group A (control feed) and group B (weevil infested feed) and fed to the experimental fishes in triplicate group twice daily at 8.00 am and 4.00 pm at 3% of their body weight. Results showed a significant deterioration (P<0.05) in the proximate composition of weevil infested feed compared to the control feed. Mean fecundity of fish fed the control diet (27,440 ± 670.03 eggs) was significantly higher (P<0.05) than fish fed weevil infested feed (19,100 ± 650.00 eggs). A linear relationship and positive significant correlation (P>0.05) were obtained between fecundity of C. gariepinus fed the two diets and body parameters (total length, body weight, ovary weight, and mean egg diameter) except total length and total weight of fish fed weevil infested feed which showed a negative significant (P<0.05) relationship. Mean female gonad weight, female GSI and male gonad weight of fish fed the control was significantly better (P < 0.05) than fish fed weevil infested feed whereas male GSI showed no significant (P > 0.05) variation. Histological examination showed that the interstitial cells of the testes and oocytes were fully matured and normally distributed Based on these findings, infestation of weevil in fish feed may lead to loss or deterioration of feed condition, quality, palatability, odor, and taste which may affect feed acceptability. It is concluded that to obtain high fecundity and a better gonad development, weevil infested feed should be avoided. Feed should be stored in a good hygienic and sanitary conditions and infested feed should be destroyed with a serious implementation of sanitation and prevention practices to prevent the infestation from recurrence.
Keywords: Weevil Infested Feed; Fecundity; Gonadal Development; Clarias gariepinus; Oocytes; Testes